Aphrodite, Demeter, Hermes and Poseidon in the Decapolis - Ovadiah, Asher (Liber annuus, 2018)
The four deities of the Greek pantheon presented in this article, and which were also adopted in the Roman period, were venerated and worshipped in the following cities of the Decapolis: Beth Shean/Scythopolis, Capitolias, Damascus, Dion, Gadara, Gerasa, Pella and Philadelphia (Amman). As evinced by the findings of sculpture, epigraphy, numismatics and gems, the cults of all four gods were clearly present in these cities during the Roman period, although evidence pertaining to the cult of Poseidon/Neptune appears to be scarce. It should be noted that no architectural remains (temples) in honour of these deities have been uncovered to date.